Portable shoe integrated instrumentation for gait analysis measurement using mems based devices - Norantanum Abu Bakar (School of Microelectronic Engineering, 2013)
This research is aimed at developing such system but using MEMS sensor and system component purchase off-the-shelf to prove the concept.